Evaluation of Propofol as Procedural Sedative Agent for Ease of Induction of Spinal Anesthesia in Patients Undergoing Abdominal Surgeries - Manasa S; Yuvaraj M K; Hosagoudar, Pradeep (Academia Anesthesiologica International, 2021)
Background: Sometimes it is difficult to position the patients for spinal anaesthesia. Poor positioning causes discomfort to both anesthesiologist and patient. It may also lead to, autonomic fluctuations. Providing procedural sedation may alleviate those undesired difficulties. In this study, we are evaluating propofol as procedural sedative agent for ease of induction of spinal anaesthesia. Subjects and Methods: This prospective study was conducted among 60 patients who were randomly divided into 2 groups. Group A received Inj Propofol 0.7mg/kg as procedural sedative agent prior to spinal anaesthesia, Group C did not receive any procedural sedative drugs. Ease of identification of space, time to induce spinal anaesthesia, number of attempts, patient comfort score, patient satisfaction score were recorded and analyzed. Results: Demographic data were comparable between the groups, there was no statistically significant difference between the groups in terms of ease of identification of space, number of attempts, patient comfort score and patient satisfaction score. Time to induce spinal anaesthesia was longer in Group A (35.53 15.39) and it was statistically significant compared to Group C. Conclusion: Using Propofol as procedural sedative agent may not significantly ease the induction of spinal anesthesia in patients undergoing abdominal surgeries compared to patients without sedation